Comunicação e consumo de vestígios e promessas: estudo da Coleção Nº 1, suas lógicas de produção e de arquivo - Sado, Flavia de Vasconcellos Protta (2020)
This research discusses the theme of memory, within cultural dynamics, which provide the formation of archives. The theoretical object is the production logic of archives and Collection Nº 1 as an empirical object. This collection is a set of 995 issues dated from 1947 to 2015, characterized by being the first copies donated by José Francisco Queiroz to the Escola Superior de Propaganda and Marketing (ESPM). In an attempt to answer the following research problem: how the production logic of archives for the consumption of memory is materialized in Collection Nº 1, we use the phenomenological theory of memory by Ricoeur (2007), the theory of Semiotics of Culture (LOTMAN, 1996, 2009) and the cultural circuits developed by Johnson (1986; 2006). We have as a general objective to map the production logic of Collection Nº 1 and the principles that make it understood as an archive and as specific objectives to define what we mean by collection and present what Collection Nº 1 consists of and how it was formed; contextualize the Collection Nº 1 as part of a semiosphere and a cultural circuit intending the process of treatment of the information of the referred collection and its insertion in the ESPM library system, with the concepts of archive and document; list conceptual spheres that imply both the weaving of memory and the production logic of archives and exemplify them with the universe of Collection Nº 1. The research is characterized by being a theoretical work that makes use of bibliographic references in the construction of its arguments and points in its empirical object the materiality of the concepts and processes covered. The participant observation methodology runs through all the work by demonstrating the operational processes carried out in the way they were experienced. The result of conceiving Collection Nº 1 as an archive is due not only to the needs of the collector but to a common desire of all human beings do not want to lose the memories and knowledge acquired throughout life, together with the concern that in the future others can have this information available. This drive to produce files begins when we show the fragility and ephemerality of our memory than the need to support it in other materialities.